Pengaruh Good Governance dan Budaya Organisasi pada Kinerja Aparatur Penyelenggara Pemerintahan Desa di Kota Denpasar - Raheni, Ni Putu Rika; Asri Dwija Putri, I.G.A.M (E-Jurnal Akuntansi, 2019)
This study aims to examine the effect of good governance and organizational culture on the performance of village government administrators in the city of Denpasar. The number of service villages in the city of Denpasar is 27 villages. Respondents in this study were village officials among others, Village Heads, Village Secretaries, Finance Chiefs, Village Consultative Bodies (BPD), and Community Empowerment Institutions (LPM) in each each village in the city of Denpasar. The number of samples obtained was 70 respondents using probability sampling methods with Slovin techniques. The data collection method used in this study was a questionnaire. The data analysis technique performed is the analysis of Multiple Linear Regression. Based on the analysis conducted, the results of this study indicate Good Governance and Organizational Culture have a positive effect on the Performance of Village Government Organizing Apparatus in the City of Denpasar. Keywords : G ood g overnance, o rganizational c ulture, a pparatus p erformance.